Raman Spectroscopy, X-Ray, SEM, and DTA Analysis of Alkali-Phosphate Glasses Containing WO3 and Nb2O5 - L. Bih; M. Azrour; B. Manoun; M. P. F. Graça; M. A. Valente (Journal of Spectroscopy)
New phosphate glasses in the quaternary system (50-x) A2O-x WO3-10 Nb2O5-40 P2O5, with x = 0; 30 and A = Li or Na were prepared by the melt quenching method. The effect on the crystallization behaviour of the glass due to the introduction of WO3 into the glass composition and, consequently, the diminishing of the molar amount of the alkaline oxide and the decreasing of the molar ratio between network modifiers and network formers (M/F) was studied. The prepared glasses were heat-treated in air, at 550°C, 600°C, and 650°C for 4 hours. The structure, of the obtained samples, was studied by differential thermal analysis (DTA), X-ray powder diffraction (XRD), and Raman spectroscopy and the morphology by scanning electron microscopy (SEM). It was found that the replacement of Li2O or Na2O by WO3 reduces the number of the crystallised phases. In the lithium-niobiophosphate glasses, the presence of WO3 promotes the formation of NbOPO4 instead of the LiNbO3 phase and reduces the formation of ortho- and pyro-phosphate phases. The thermal treatments affect the arrangements of the network structure of the AW40-glasses.